The effects of law through actions of inspections - Pečarič, Mirko (Mednarodna revija za javno upravo, 2017)
Regulated phenomena in changing environments are difficult to manage. Their complexity is many times higher that can usually be embraced in the conventional ways public administrations prepare draft statutes, adjudicate and control other people. The same or even more stands for inspections as public bodies that directly see 'regulations in action', how asymmetries between regulation and implementation arise. Inspection is in the context of executive tasks despite its age a relatively new and poorly understood element of regulatory policies. This paper claims that regulation and enforcement are two sides of the same coin: only 'regulation-enforcement' (feed-in) and 'enforcement-regulation' (feedback) are the 'eyes and ears' of effective regulation. Without the latter, when rules are realistic and adequate for a given context, no amount of enforcement will make unrealistic rules work. At the same time, without the properly administrated enforcement steps, focused on the risk-analysis, risk-management (risk-based strategic planning), monitoring and sufficient resources, no amount of otherwise good regulation will provide expected results.
Keywords: inspections; inšpekcijski nadzor; javna uprava; public administration